The imminent epidemic of atrial fibrillation and its concomitant diseases – Myocardial infarction and heart failure - A cause for concern - Börschel, Christin S.; Schnabel, Renate B. (International journal of cardiology, 2019)
Atrial fibrillation (AF) is increasingly common in the general population. It often coincides with myocardial infarction (MI) and heart failure (HF) which are also diseases in older adults. All three conditions share common cardiovascular risk factors. While hypertension and obesity are central risk factors for all three diseases, smoking and diabetes appear to have less impact on AF. To date, age is the single most important risk factor for AF in the general population. Further, epidemiological studies suggest a strong association of AF to MI and HF. The underlying pathophysiological mechanisms are complex and not fully understood. Both MI and HF can trigger development of AF, mainly by promoting structural and electrical atrial remodeling. On the other hand, AF facilitates HF and MI development via multiple mechanisms, resulting in a vicious circle of cardiac impairment and adverse cardiovascular prognosis. Consequently, to prevent and treat the coincidence of AF and HF or MI a strict optimization of cardiovascular risk factors is required. •MI and HF are frequent comorbidities of AF.•All three are associated to common cardiovascular risk factors.•Population-attributable risks of cardiovascular risk factors differ between AF, MI and HF.•Coincidence of AF and MI or HF comes with an adverse prognosis.•Prevention by improved management of known risk factors is essential.